Tilings of the Sphere with Right Triangles II: The $(1,3,2)$, $(0,2,n)$ Subfamily - Dawson, Robert J. MacG.; Doyle, Blair (The Electronic Journal of Combinatorics, 2006)
Sommerville and Davies classified the spherical triangles that can tile the sphere in an edge-to-edge fashion. Relaxing this condition yields other triangles, which tile the sphere but have some tiles intersecting in partial edges. This paper shows that no right triangles in a certain subfamily can tile the sphere, although multilayered tilings are possible.